Zróżnicowanie somatyczne i typologiczne studentów i studentek pierwszego roku wychowania fizycznego Uniwersytetu Zielonogórskiego = Somatic and typological differentiation of first year male and female students of physical education, University of Zielona Gora - Asienkiewicz, Ryszard; Wieliński, Dariusz; Wieczorek, Dariusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the paper is to present somatic and typological differentiation of the academic youth studying Physical Education at the University of Zielona Gora as well as the comparative characteristics with other universities in Poland.
Keywords: academic youth; physical development; comparative; młodzież akademicka; rozwój fizyczny; porównania